ISLAMIC SECURITIES CROWDFUNDING RESEARCH: A BIBLIOMETRIC ANALYSIS - Tafitri, Ulviya; Ulviya Tafitri; Aniva Nur Fadhilah; Muhammad Syafii Antonio (Airlangga International Journal of Islamic Economics and Finance, 2023)
The number of publications concentrating on Islamic Fintech and Securities Crowdfunding has significantly increased in recent years, especially from 2017 to 2023. Through bibliometric analyses using Dimension.ai, a dependable platform for accessing registered titles and abstracts, this growing interest has been thoroughly investigated. This investigation's main goal is to identify common topics and writing styles among the authors in this sector. The most recent information for this analysis was obtained by using the search term "Islamic Securities Crowdfunding" on the Dimension.ai platform on September 26, 2023. Many publications have made significant contributions to this increase in research output. A well-known work in this field, "The Crowdfunding and Islamic Securities: The Role of Financial Literacy," offers insightful information on how crowdfunding and Islamic securities interact. Further highlighting their importance and prevalence in the discourse around Islamic Securities Crowdfunding is the frequent use of the terms "Research," "Study," "Platform," and "Technology." This study highlights the most productive authors who have contributed to the academic environment in this area and examines the current trends. In conclusion, it is believed that the knowledge gained from this study would inform the future endeavors of academics and professionals working in this field. Keywords: Islamic Securities Crowdfunding, Islamic Fintech, Bibliometric, Islamic Finance